Molecular detection and characterization of Anaplasma marginale infecting cattle, buffalo, and camel populations in southern Egypt - Mahmoud, Hassan Y. A. H.; Ali, Alsagher O.; Tanaka, Tetsuya (Frontiers in Veterinary Science, 2023)
Anaplasmosis is a severe tick-borne disease of ruminants caused by Anaplasma marginale. A. marginale is distributed worldwide and attacks erythrocytes, resulting in increased body temperature, anemia, jaundice, abortion, and, in some cases, death. Animals infected with this pathogen become life-long carriers. In the present study, we aimed to detect and characterize A. marginale isolated from cattle, buffalo, and camel populations using novel molecular techniques in southern Egypt. 250 samples (from 100 cattle, 75 water buffalo, and 75 camel) were analyzed by PCR for the presence of Anaplasmataceae, specifically A. marginale. The animals varied in breed, age, and gender, with most showing no signs of severe disease. By species, A. marginale was 61/100 (61%) in cattle, 9/75 (12%) in buffalo., and only 5/75 (6.66%) in camel. All A. marginale-positive samples were examined for the heat-shock protein groEL gene and, additionally for major surface protein 4 (msp4) and major surface protein 5 (msp5) genes to enhance specificity. Phylogenetic analysis of A. marginale targeted three genes (groEL, msp4, and msp5). This study provides the first report on using three genes for A. marginale detection in Camelus dromedarius in southern Egypt and had generated new phylogenetic data for A. marginale infections in camel. Anaplasma marginale infection is endemic in different animal species in southern Egypt. Screening herds for A. marginale is recommended even when the signs of anaplasmosis are absent.